Biology Education Research: Lessons and Future Directions - Singer, Susan R. (American Society for Cell Biology, 2013)
This feature draws on a 2012 National Research Council report to highlight some of the insights that discipline-based education research in general—and biology education research in particular—have provided into the challenges of undergraduate science education. It identifies strategies for overcoming those challenges and future directions for biology education research.